Increased Protein Tyrosine Phosphatase 1B (PTP1B) Activity and Cardiac Insulin Resistance Precede Mitochondrial and Contractile Dysfunction in Pressure‐Overloaded Hearts. Issue 13 (3rd July 2018) - Nguyen, T. Dung; Schwarzer, Michael; Schrepper, Andrea; Amorim, Paulo A.; Blum, Daniel; Hain, Claudia; Faerber, Gloria; Haendeler, Judith; Altschmied, Joachim; Doenst, Torsten
Abstract : Background: Insulin resistance in diabetes mellitus has been associated with mitochondrial dysfunction. Defects at the level of mitochondria are also characteristic of heart failure. We assessed changes in cardiac insulin response and mitochondrial function in a model of pressure overload‐induced heart failure. Methods and Results: Rats underwent aortic banding to induce pressure overload. At 10 weeks, rats showed cardiac hypertrophy and pulmonary congestion, but left ventricular dilatation and systolic dysfunction were only evident after 20 weeks. This contractile impairment was accompanied by mitochondrial dysfunction as shown by markedly reduced state 3 respiration of isolated mitochondria. Aortic banding did not affect systemic insulin response. However, insulin‐stimulated cardiac glucose uptake and glucose oxidation were significantly diminished at 10 and 20 weeks, which indicates cardiac insulin resistance starting before the onset of mitochondrial and contractile dysfunction. The impaired cardiac insulin action was related to a decrease in insulin‐stimulated phosphorylation of insulin receptor β. Consistently, we found elevated activity of protein tyrosine phosphatase 1B (PTP1B) at 10 and 20 weeks, which may blunt insulin action by dephosphorylating insulin receptor β. PTP1B activity was also significantly increased in left ventricular samples of patients with systolic dysfunction undergoing aortic valve replacement because of aortic stenosis. Conclusions: Pressure overload causes cardiac insulin resistance that precedes and accompanies mitochondrial and systolic dysfunction. Activation of PTP1B in the heart is associated with heart failure in both rats and humans and may account for cardiac insulin resistance. PTP1B may be a potential target to modulate insulin sensitivity and contractile function in the failing heart.